In vivo Pharmacokinetic Drug-Drug Interaction Studies Between Fedratinib and Antifungal Agents Based on a Newly Developed and Validated UPLC/MS-MS Method - Tang, Congrong; Niu, Xiaohui; Shi, Lu; Zhu, Huidan; Lin, Guanyang; Xu, Ren-ai (Frontiers in Pharmacology, 2021)
In the present study, a sensitive, simple and fast bioanalytical method involving ultra performance liquid chromatography tandem mass spectrometry (UPLC-MS/MS) technique for the detection of fedratinib concentrations in rat plasma was optimized and established, and was used to describe the pharmacokinetic changes of fedratinib after oral treatment with antifungal drugs (isavuconazole, posaconazole, fluconazole and itraconazole). The purpose of chromatographic separation of fedratinib and the internal standard (IS, bosutinib) was accomplished using an Acquity UPLC BEH (2.1 mm × 50 mm, 1.7 μm) reverse-phase C18 column under a linear gradient elution of the mobile phase, which was composed of acetonitrile (solution A) and water with 0.1% formic acid (solution B), along with a flow rate of 0.40 mL/min. The analyte and IS were measured with electrospray ion (ESI) source in positive ion mode on a XEVO TQS triple quadrupole tandem mass spectrometer. The new UPLC-MS/MS method displayed enough linearity at the calibration curve range of 0.5-500 ng/mL for fedratinib. The intra- and inter-day of accuracy and precision were assessed and validated to meet the requirements for the guidelines of bioanalytical method. And, the results of matrix effect, recovery, and stability were all within the acceptable limits. The newly developed UPLC-MS/MS assay was forward successfully used to describe the pharmacokinetic changes of fedratinib in rats in the present of antifungal drugs (isavuconazole, posaconazole, fluconazole and itraconazole). It turned out that fluconazole resulted in a prominent inhibitory effect on the metabolism of fedratinib, followed by treatment with itraconazole and isavuconazole. Therefore, the toxicity of fedratinib should be avoided when the concurrent use of fedratinib with CYP3A4 inhibitors may occur.